The Description of Sleep Disorder In Nursing Students At Padjadjaran University Who Experience Smartphone Addiction - Atika Salma Azzahra; Ati Surya Mediawati; Nur Oktavia Hidayati (Faculty of Nursing, Universitas Jember, 2021)
Background: Sleep disorders can be experienced by college students, including nursing students. Nursing students are prospective professional nurses, if they experience sleep disorders it is feared that it will have a negative impact during lectures and health services that will be provided when becoming a nurse later. Purpose: This study aims to determine the description of sleep disorders in nursing students at Padjadjaran University who experience smartphone addiction. Methods: The method used in this research was quantitative descriptive method. The population in this research was the nursing students of Padjadjaran University, with a total of 668 respondents using purposive sampling technique, obtained a total sample of 400 respondents. The instrument used in this study was the Sleep Disorders Symptom Checklist-17 (SDS-CL-17). The data obtained were analyzed using univariate analysis with results presented in percentage. Results: The result of this study showed that the majority of respondents (99.8%) experienced sleep disorders. Based on the sleep disorders category, the majority of respondents experienced circadian rhythmic sleep-wake disorder (91.8%) and parasomnia (76%), while less than half of the respondents also experienced insomnia (46.2%), narcolepsy (45.8 %), sleep-related movement disorders (36.2%) and obstructive sleep apnea (30.8%) and experienced two or more sleep disorders (89%). Conclusion: The high incidence of sleep disorders indicated the need for preventive, promotive, curative and rehabilitative solutions for nursing students to reduce the impact that can be caused in the future.